Mapping urban heat island phenomenon: Remote sensing approach - Noorazuan, Md. Hashim; Asmala, Ahmad; Mardina, Abdullah (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/